AKAD MUSYARAKAH DAN PENERAPAN DALAM MANAJEMEM PERBANKAN SYARIAH - Nazwa, Puteri Nurhafizah; Hasbi, M. Zidny Nafi' (IJMA (Indonesian Journal of Management and Accounting), 2021)
Islamic banks are banks that serve the community whose process is in accordance with Islamic teachings. One of the contracts in Islamic banks is the Musharakah contract. Musyarakah contract is a collaboration contract of two or more partners by combining their capital in a particular project or business, and the profit sharing is divided according to the agreement and the risk is shared. The implementation of musharakah contracts in Islamic banks is that Islamic banks and ijab qabul partners combine their capital to make a project or business by agreeing on the distribution of profits later from the project or business carried out and ready to share the risk if there is a loss later.